Comparison of three different techniques of endotracheal tube cuff inflation: just seal, stethoscope guided and pressure volume loop: a prospective randomized study - Bhardwaj, Mamta; Kaur, Kiranpreet; Sharma, Asha; Kumar, Prashant; Tobria, Raj; Saini, Savita (International Journal of Research in Medical Sciences, 2020)
Background: Cuffed endotracheal tubes not only ensure a proper seal during positive pressure ventilation, but at the same time also prevent aspiration of gastric secretions. The aim of this prospective, randomized study was to compare three methods of ETT cuff inflation-- palpation of the leak in suprasternal notch (Just seal), a stethoscope guided method of tracheal tube cuff inflation and PVL guided cuff inflation. Methods: After approval by institutional ethical committee, 192 patients of either sex in age group of 18-50 years belonging to ASA physical status I or II were enrolled. Each patient was randomly allocated into one of three groups: one group received standard 'just seal' method of tracheal cuff inflation (JS), the second group, the stethoscope-guided method (SG) and in third group cuff was inflated using Pressure Volume Loop (PVL). Volume of air introduced into the cuff and pressure within the cuff was recorded. Results: A total of 192 patients were recruited to the study. The median (IQR [range]) tracheal cuff pressure was 12 (10-22 [6-28]) cm H2O, 16 (12-24[6-38]) and 14 (10-22[8-32]) cmH2O in JS, SG and PVL group respectively. Cuff pressures within the recommended range of 20-30 cm H2O fell in 25% of the patients in both JS and SG group and 31% patients in PVL group. The mean volumes of air introduced in the cuff and the resultant mean cuff pressure in all groups was found to be statistically insignificant (p= 0.4, 0.18 respectively). Tidal volume discrepancy was more and 75% of cuff pressures were less than the recommended range in JS than the other two groups. Conclusions: Real time PVL displayed on most modern anaesthesia machine is a good alternative to check for proper ETT cuff inflation, avoid high cuff pressure and monitor air leak.